2012
DOI: 10.1111/ibi.12008
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence that distinct song phrases in the Grey‐cheeked Fulvetta Alcippe morrisonia permit species and local dialect recognition

Abstract: Birds with small song repertoires have a limited number of song types which may serve multiple functions. The Grey-cheeked Fulvetta Alcippe morrisonia is a non-migratory species of lowland forests in Taiwan. Its song consists of two distinct phrases: a whistled phrase and a harmonic one. Each individual usually sings only one type of whistled phrase, and the geographical patterns of songs can be distinguished by the motif of this phrase. We proposed a dual adaptation hypothesis for the functions of these two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(23 reference statements)
2
3
0
Order By: Relevance
“…A similar segregation of information about local dialect and species recognition was suggested for the grey‐cheeked fulvetta ( Alcippe morrisonia ) (Shieh et al. ). Briefer et al.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A similar segregation of information about local dialect and species recognition was suggested for the grey‐cheeked fulvetta ( Alcippe morrisonia ) (Shieh et al. ). Briefer et al.…”
Section: Discussionsupporting
confidence: 60%
“…Males respond more strongly to neighbour song in which the note complex is replaced with a copy from a stranger. A similar segregation of information about local dialect and species recognition was suggested for the grey-cheeked fulvetta (Alcippe morrisonia) (Shieh et al 2013). Briefer et al (2008) showed experimentally that skylarks (Alauda arvensis), a species with continuous song and a huge repertoire of syllables, share some phrases as a group signature for N-S discrimination.…”
Section: Discussionsupporting
confidence: 54%
“…Unlike those large‐repertoire species, the grey‐cheeked fulvetta has a small repertoire; one individual produces only 1–2 song types (Shieh 2004). Nevertheless, this species can produce songs consisting of two phrases with distinct acoustic structures, transmitting local dialect information for long‐range communication and species information for short‐range communication (Shieh et al 2013). Including two distinct phrases in a song ensures that they are sung within the same acoustic environment, including the same noise levels and microhabitats.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, there were more counter‐singing responses to familiar whistled phrases than foreign ones for territorial advertisements in long‐range communication. In contrast, both familiar and foreign harmonic phrases elicited similar approaching responses in short‐range communication (Shieh et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of geographic markers in acoustic signals have been shown repeatedly in bird songs (Nottebohm 1969;Mundinger 1982;Zimmermann et al 2016). The richness of avian vocal repertories offer a wide range of possibilities for differentiation of geographic markers: changes in note combinations, presence or absence of some notes (particularly during new population finding) and/or rhythm of emission of different notes (Baker and Jenkins 1987;Handford 1988;Shieh et al 2013). Nevertheless, such markers have also been found within single stereotyped acoustic elements, e.g.…”
Section: Discussionmentioning
confidence: 99%